Highly Integrated, Wearable Carbon‐Nanotube‐Yarn‐Based Thermoelectric Generators Achieved by Selective Inkjet‐Printed Chemical Doping. Issue 25 (1st May 2022) - Park, Kyung Tae; Cho, Young Shik; Jeong, Inho; Jang, Doojoon; Cho, Hyeon; Choi, Yoohyeon; Lee, Taemin; Ko, Youngpyo; Choi, Jaeyoo; Hong, Soo Young; Oh, Min‐Wook; Chung, Seungjun; et al.
Abstract: Flexible thermoelectrics that enable conformal contact with heat sources of arbitrary shape are indispensable for self‐powered wearable electronics. Scalable integration of flexible thermoelectric (TE) materials into functional devices has improved over the past few years, however, the practical applications of flexible TE materials are still hindered by low performance. Herein, highly aligned carbon‐nanotube yarns (CNTYs) are proposed, combined with selective doping via picoliter scale inkjet printing. Coagulation assisted by van der Waals forces ensures a highly aligned structure of the CNTY, thus achieving the ultrahigh power factors of 4091 and 4739 µW m −1 K −2 for the p ‐ and n ‐type, respectively. The proposed TE materials can be effortlessly up‐scaled into highly integrated modules via inkjet printing. A highly integrated, flexible CNTY‐based TE generator (TEG) with 600 PN pairs generates unparalleled milliwatt‐scale power at Δ T  = 25 K, which is a few orders of magnitude higher than those of previously reported flexible material‐based TEGs. This TEG successfully powers a red light‐emitting diode using body heat alone, requiring no external power sources. For the seamless operation of practical applications requiring high power, this work explores the key design parameters for flexible TEGs with high performance and manufacturability and presents new platforms for self‐powered wearable electronics. Abstract : Flexible thermoelectrics (TE) that enable conformal contact with heat sources of arbitrary shape are indispensable for self‐powered wearable electronics. The authors propose highly aligned carbon‐nanotube yarns combined with selective doping via picoliter scale inkjet printing, offering effortless scale‐up into highly integrated modules. The TE module with 600 PN pairs generates unparalleled milliwatt‐scale power at Δ T  = 25 K.